2012
DOI: 10.1017/s1751731112000225
|View full text |Cite|
|
Sign up to set email alerts
|

Reevaluation of vitamin E supplementation of dairy cows: bioavailability, animal health and milk quality

Abstract: Although vitamin E has been known as an essential nutrient for almost 80 years, we are far from a complete understanding of all the aspects related to bioavailability and its effects on health and milk quality in dairy cows. Vitamin E is a generic descriptor for two families of lipid-soluble compounds, the tocopherols and the tocotrienols, of which a-tocopherol has the highest biological activity. Commercially available a-tocopherol supplements for dairy cows contain either the natural RRR form or the syntheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
67
2
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(82 citation statements)
references
References 30 publications
7
67
2
6
Order By: Relevance
“…Therefore, we are measuring the cumulative capacity of the antioxidant defense against a particular oxidant aggression (how the animal has been accumulating and disposing its antioxidants reserves to specific, predictable and expected situations such as delivery and early lactation), rather than measure the short-term antioxidants at the time of sampling. The prepartum period is characterized by a depleted antioxidant status and, consequently, OS (Bernabucci et al, 2002 and, and therefore these cows were supplemented with a vitamin complex before parturition, which is a recommended practice to minimize the risk of postpartum diseases (Politis, 2012). This fact prevents us from getting the clear picture of the natural cycle of OSi; however, on the other hand, it shows the oxidative status that might be observed in dairy cows in commercial farms.…”
Section: Antioxidantsmentioning
confidence: 99%
“…Therefore, we are measuring the cumulative capacity of the antioxidant defense against a particular oxidant aggression (how the animal has been accumulating and disposing its antioxidants reserves to specific, predictable and expected situations such as delivery and early lactation), rather than measure the short-term antioxidants at the time of sampling. The prepartum period is characterized by a depleted antioxidant status and, consequently, OS (Bernabucci et al, 2002 and, and therefore these cows were supplemented with a vitamin complex before parturition, which is a recommended practice to minimize the risk of postpartum diseases (Politis, 2012). This fact prevents us from getting the clear picture of the natural cycle of OSi; however, on the other hand, it shows the oxidative status that might be observed in dairy cows in commercial farms.…”
Section: Antioxidantsmentioning
confidence: 99%
“…It may therefore seem surprising that VitE supplements are routinely recommended to counteract the detrimental effect of ROS in dairy herds. Since the real antioxidant need might well vary with the individual, a standard dose may not always be suitable (Politis, 2012;Dimri et al, 2013), particularly in the dry period.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, SSC is one of the significant factors that determine milk price as it is considered as a gauge for the hygienic quality of milk. A review by Politis (2012) suggested that dietary vitamin E can improve milk quality either by directly enhancing the oxidative stability of milk or by indirectly reducing the level of SSC and plasmin activity in milk. Dietary antioxidants including vitamin E, Se and other trace minerals could reduce the occurrence of intramammary infection and thus decrease the SSC in milk (Baldi et al, 2000;Politis et al, 2004;Machado et al, 2013).…”
Section: Milkmentioning
confidence: 99%